Education and training in addiction medicine and psychology across Europe: a EUFAS survey - Bramness, Jørgen Gustav; Leonhardt, Marja; Dom, Geert; Batalla, Albert; Flórez Menéndez, Gerardo; Mann, Karl; Wurst, Friedrich Martin; Wojnar, Marcin; Drummond, Colin; Scafato, Emanuele; Gual, Antoni; Ribeiro, Cristina Maria; et al. (European addiction research, 2023)
Introduction: Training in addiction medicine and addiction psychology is essential to ensure the quality of treatment for patients with substance use disorders. Some earlier research has shown varying training between countries, but no comprehensive study of addiction training across Europe has been performed. The present study by the European Federation for Addiction Societies (EUFAS) aimed to fill this gap. Methods: A Delphi process was used to develop a questionnaire on specialist training in addiction treatment in 24 European countries. The final questionnaire consisted of 14 questions on either addiction medicine or addiction psychology, covering the nature and content of the training and institutional approval, the number of academic professorial positions, and the estimated number of specialists in each country. Results: Information was not received from all countries, but six (Belgium, Denmark, Ireland, Italy, Poland, and Romania) reported no specialized addiction medicine training, while 17 countries did. Seven countries (Belgium, France, Ireland, Italy, Russia, Switzerland, and the Netherlands) reported no specialized addiction psychology training, while 14 countries did. Training content and evaluation methods varied. Approval was given either by governments, universities, or professional societies. Eighteen countries reported having professorships in addiction medicine and 12 in addiction psychology. The number of specialists in addiction medicine or psychology varied considerably across the countries. Discussion: The survey revealed a large heterogeneity in training in addiction medicine and addiction psychology across Europe. Several countries lacked formal training, and where formal training was present, there was a large variation in the length of the training. Harmonization of training, as is currently the case for other medical and psychology specializations, is warranted to ensure optimal treatment for this under-served patient group.